The Influence of Interactive Learning Using Video Quizizz and Mind Mapping on the Understanding of the Indonesian Story Social Studies Material - Ufi Islachah; Isa Anshori (Journal La Sociale, 2026)
This study aims to determine the effect of interactive learning using Quizizz videos and mind mapping techniques on the understanding of Social Sciences (IPS) material on the theme of Indonesian Stories at MI Raden Rahmat Wonokromo Surabaya. Interactive learning is an approach that involves students engaging with digital media and utilizing fun visual strategies. Quizizz is an interactive digital quiz platform, and mind mapping is a visual note-taking technique that is believed to improve students' understanding of narrative and conceptual materials. The research method used is quantitative with an associative approach. The research sample was all sixth-grade students who were analyzed using multiple linear regression. The results showed that both Quizizz videos and mind mapping had a significant effect, partially and simultaneously, on students' understanding. The R² value of 0.975 indicates that 97.5% of the understanding of IPS material is influenced by these two variables. Thus, the integration of technology and visual strategies has proven effective in improving the quality of IPS learning in madrasah.